Two-dimensional porous nano NiFe2O4 and preparation method of self-repairing noise-reducing anticorrosive coating of two-dimensional porous nano NiFe2O4
Regular two-dimensional porous nano NiFe2O4 is prepared through hydrothermal synthesis, and combined with polyurethane matrix to introduce dynamic disulfide bonds, solving the problem that noise reduction coatings in the prior art are difficult to achieve self-healing, and achieving excellent noise reduction and multiple cycle photothermal self-healing performance.
Patent Information
- Application Number
- CN202510128391.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to achieve materials with good acoustic performance and self-healing functions in noise reduction coatings, especially in the application of NiFe2O4, poor morphology of the two-dimensional porous structure affects performance.
Two-dimensional porous nanoniFe2O4 with regular two-dimensional layered structure and large specific surface area were prepared by hydrothermal synthesis method, and combined with polyurethane matrix to introduce covalent bonds such as dynamic disulfide bonds to improve the corrosion and noise reduction performance of the coating.
It realizes the effective application of two-dimensional porous nano NiFe2O4 in the field of noise reduction, and has the ability to self-heal the photothermal recovery during multiple cycles, solving the problem that traditional coatings are difficult to protect for a long time.
Smart Images

Figure CN119842307A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of synthesis of inorganic materials and polymer material organic coatings, and in particular to a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise-reducing and anti-corrosion coating thereof. Background Art
[0002] NiFe2O4 is a typical spinel ferrite material with good chemical stability and excellent magnetic properties. Its unique structure makes it have wide application potential in many fields. In recent years, researchers have prepared NiFe2O4 with a porous structure through methods such as hydrothermal synthesis. This structure not only increases the specific surface area of the material, but also enhances its porosity, thus providing a better performance basis for various applications.
[0003] In the field of noise reduction coatings, the pore structure and specific surface area of the material are key factors affecting its acoustic performance. NiFe2O4 with a two-dimensional porous structure can effectively absorb and scatter sound waves due to its abundant pores and large specific surface area. When this material is added to a noise reduction coating as a filler, its porous structure can increase the porosity of the coating, thereby improving the coating's ability to absorb sound waves. In addition, the magnetic properties of NiFe2O4 can also enhance the electromagnetic shielding performance of the coating to a certain extent, which is of great significance for application scenarios that require both noise reduction and shielding functions. Although various methods can currently synthesize NiFe2O4 with different morphologies and structures, the morphology of the obtained two-dimensional porous structure is poor, which in turn affects the performance.
[0004] Coatings face the problem of corrosion and breakage. In recent years, the research and development of self-healing coatings that can repair damage by themselves after being damaged has become one of the frontier research hotspots in the field of corrosion and protection. The self-healing function is mainly achieved by means of film-forming substances or corrosion inhibitors embedded in the organic coating, as well as the reversible or dynamic bonds inherent in the organic coating. However, once the pre-embedded film-forming substances or corrosion inhibitors are exhausted, the self-healing ability of the coating disappears. In this regard, the demand for self-healing coatings based on reversible or dynamic bonds is very urgent. Among them, dynamic disulfide bonds have received more widespread attention because they can undergo exchange reactions at moderate temperatures. Therefore, it is urgent to invent an anti-corrosion organic coating based on a noise-reducing filler with photothermal properties, which has both low cost and excellent photothermal self-healing properties. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a simple hydrothermal synthesis method of two-dimensional porous nano NiFe2O4. The innovations of the present invention are mainly in the following aspects:
[0006] 1. NiFe2O4 has a regular two-dimensional layered stacking arrangement, is evenly distributed and has a large specific surface area.
[0007] 2. By introducing other covalent bonds such as dynamic disulfide bonds, the polyurethane matrix is provided with self-healing properties, thereby improving the anti-corrosion performance of the coating. At the same time, the breaking and recombination of disulfide bonds drives the movement of the molecular chains, thereby improving the damping and noise reduction performance of the coating.
[0008] In order to achieve the above technical objectives, the present invention is implemented by the following technical means:
[0009] 1. A method for preparing a two-dimensional porous nano NiFe2O4 and its self-repairing noise reduction and anti-corrosion coating, the specific steps are as follows:
[0010] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is:
[0011] 1.1) Weigh nickel chloride hexahydrate and ferric chloride hexahydrate in a molar ratio of 1:2 and dissolve them in 80 ml of deionized water;
[0012] 1.2) stirring the above solution at a rotation speed of 200-800 rpm for 10-40 minutes, and subjecting the mixed solution to ultrasonic treatment for 5-20 minutes to obtain a mixed metal ion solution;
[0013] 1.3) adding a precipitant to the above metal ion solution, and repeating the stirring and ultrasonic operation;
[0014] 1.4) transferring the solution to a sealed reactor for reaction, keeping the temperature in the range of 120-200° C. for 6-18 hours, washing the solution by centrifugation with deionized water and anhydrous ethanol at 6000 rpm for several times after cooling, and vacuum drying the solution at 60° C. for 12 hours to obtain a two-dimensional porous nano NiFe2O4 precursor powder;
[0015] 1.5) calcining the dried two-dimensional porous nano-NiFe2O4 precursor powder at 800° C. in a tube furnace for 2 hours to obtain a two-dimensional porous nano-NiFe2O4 powder;
[0016] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1. The specific operation steps are as follows:
[0017] 2.1) Add polyester diol into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0018] 2.2) Cool down to 70°C, add the solvent, diisocyanate and catalyst dropwise into the three-necked flask, and stir at 300-800 rpm for 1-3 hours;
[0019] 2.3) Raise the temperature to 80°C, dissolve the disulfide in the solvent, ultrasonicate for 5-10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300-800 rpm for 3-6 hours;
[0020] 3) Preparation of self-repairing anti-corrosion coating: Add the two-dimensional porous nano-NiFe2O4 to the above polyurethane system in a mass ratio of 0.01-0.1:1 between the two-dimensional porous nano-NiFe2O4 and the polyurethane matrix, and stir with a mechanical stirrer for 0.5-2 hours.
[0021] Optionally, the precipitant is any one or more of glucose, terephthalic acid, and polyvinyl pyrrolidone;
[0022] Optionally, the polyester diol is any one or more of polybutylene adipate, polyethylene adipate, polycarbonate diol, and polycaprolactone diol;
[0023] Optionally, the diisocyanate is any one or more of toluene diisocyanate, isophorone diisocyanate, hexanediol diisocyanate, dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate;
[0024] Optionally, the disulfide is any one or more of bis(2-hydroxyethyl) disulfide, bis(10-hydroxydecyl) disulfide, 2,2'-diaminodiphenyl disulfide, bis(11-hydroxyundecyl) disulfide, bis(4-(hydroxymethyl)phenyl) disulfide, and diallyl disulfide;
[0025] Optionally, the solvent is any one of tetrahydrofuran, acetone, dichloromethane, toluene, dimethylformamide, ether, and dimethylacetamide;
[0026] Optionally, the catalyst is any one of dibutyltin dilaurate, dibutyltin, tetrabutyltin, stannous octoate, and tributyltin chloride.
[0027] 2. The present invention also provides an application of a two-dimensional porous NiFe2O4 and a self-healing noise reduction anti-corrosion coating thereof. The above-synthesized self-healing anti-corrosion coating is coated on a metal substrate, cured at 60°C for 12-24 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating.
[0028] The metal substrate may be the widely used steel material, or other metal materials such as iron, copper, and aluminum.
[0029] Compared with the prior art, the beneficial effects of the two-dimensional porous nano NiFe2O4 and the preparation method of the self-repairing noise reduction and anti-corrosion coating of the present invention are as follows:
[0030] 1. The two-dimensional porous nano NiFe2O4 of the present invention has low raw material cost, simple method, regular two-dimensional stacking structure, many voids and large specific surface area, which solves the problem of difficult application of NiFe2O4 in the field of noise reduction.
[0031] 2. The present invention introduces dynamic disulfide bonds into the polyurethane matrix, and uses dynamic disulfide bonds and reversible hydrogen bonds to provide self-repairing properties for the polyurethane matrix, thereby improving the anti-corrosion performance of the coating. The breaking and recombination of the reversible dynamic bonds can drive the movement of the polyurethane molecular chains, increase the friction between the molecular chains, and improve the coating's ability to dissipate sound.
[0032] 3. Experiments have shown that the two-dimensional porous nanostructured NiFe2O4 successfully prepared by the invention is combined with a polyurethane substrate to form a composite coating. The coating exhibits excellent noise reduction capabilities and also has the characteristics of multiple cycles of photothermal self-repair, effectively overcoming the problem of traditional coatings being difficult to provide long-term protection, and showing great development potential and commercial value in the field of marine anti-corrosion coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a SEM image of NiFe2O4 synthesized in Example 1;
[0034] Figure 2 is the X-ray diffraction pattern XRD of NiFe2O4 synthesized in Example 1;
[0035] Figure 3 is a SEM image of NiFe2O4 synthesized in Example 2;
[0036] Figure 4 It is a nitrogen adsorption and desorption diagram of NiFe2O4 synthesized in Example 2;
[0037] Figure 5 is the infrared spectrum of the PU-1 coating synthesized in Example 3;
[0038] Figure 6 The optical photographs of the damaged coating and the repaired coating after the PU-3 coating prepared in Example 4 was irradiated with a near-infrared laser with a power of 1.5 W and a wavelength of 808 nm for 180 seconds;
[0039] Figure 7 The temperature rise curve of the PU-3 coating synthesized in Example 4 under 180s of near-infrared laser irradiation with a power of 1.5W and a wavelength of 808nm and the infrared thermal imaging image after 180s of irradiation;
[0040] Figure 8These are optical photographs of the damaged coating and the repaired coating after the PU-6 coating prepared in Example 5 was irradiated with a near-infrared laser with a power of 1.5 W and a wavelength of 808 nm for 180 seconds;
[0041] Fig. 9 The temperature rise curve of the PU-6 coating synthesized in Example 5 within 180 seconds of near-infrared laser irradiation with a power of 1.5 W and a wavelength of 808 nm and the infrared thermal imaging image after irradiation for 180 seconds;
[0042] Fig.10 The Nyquist analysis test results of the electrodes modified with different PU-6 coatings prepared in Example 5 after immersion for 60 days;
[0043] Fig.11 The Bode amplitude analysis test results of the electrodes modified with different PU-6 coatings prepared in Example 5 after immersion for 60 days;
[0044] Fig.12 The Bode phase angle analysis test results of the electrodes modified with different PU-6 coatings prepared in Example 5 after immersion for 60 days;
[0045] Fig.13 This is a test chart of the noise reduction capability of the PU-10 coating prepared in Example 5 in a laboratory environment;
[0046] Fig.14 The temperature rise curve of the PU-10 coating synthesized in Example 6 within 180 seconds of near-infrared laser irradiation with a power of 1.5 W and a wavelength of 808 nm and the infrared thermal imaging image after irradiation for 180 seconds;
[0047] Fig.15 These are optical photographs of the damaged coating and the repaired coating after the PU-10 coating prepared in Example 6 was irradiated with a near-infrared laser with a power of 1.5 W and a wavelength of 808 nm for 180 seconds. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with the accompanying drawings and specific implementation methods so that those skilled in the art can understand and implement the invention. Obviously, the embodiments described below are only some of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0049] The present invention provides a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof, wherein the coating is composed of a two-dimensional porous nano NiFe2O4 filler and an organic coating, and the specific steps are as follows:
[0050] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is:
[0051] 1.1) Weigh nickel chloride hexahydrate and ferric chloride hexahydrate in a molar ratio of 1:2 and dissolve them in 80 ml of deionized water;
[0052] 1.2) stirring the above solution at a rotation speed of 200-800 rpm for 10-40 minutes, and subjecting the mixed solution to ultrasonic treatment for 5-20 minutes to obtain a mixed metal ion solution;
[0053] 1.3) adding a precipitant to the above metal ion solution, and repeating the stirring and ultrasonic operation;
[0054] 1.4) transferring the solution to a sealed reactor for reaction, keeping the temperature in the range of 120-200° C. for 6-18 hours, washing the solution by centrifugation with deionized water and anhydrous ethanol at 6000 rpm for several times after cooling, and vacuum drying the solution at 60° C. for 12 hours to obtain a two-dimensional porous nano NiFe2O4 precursor powder;
[0055] 1.5) calcining the dried two-dimensional porous nano-NiFe2O4 precursor powder at 800° C. in a tube furnace for 2 hours to obtain a two-dimensional porous nano-NiFe2O4 powder;
[0056] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1. The specific operation steps are as follows:
[0057] 2.1) Add polyester diol into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0058] 2.2) Cool down to 70°C, add the solvent, diisocyanate and catalyst dropwise into the three-necked flask, and stir at 300-800 rpm for 1-3 hours;
[0059] 2.3) Raise the temperature to 80°C, dissolve the disulfide in the solvent, ultrasonicate for 5-10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300-800 rpm for 3-6 hours;
[0060] 3) Preparation of self-repairing anti-corrosion coating: Add the two-dimensional porous nano-NiFe2O4 to the above polyurethane system in a mass ratio of 0.01-0.1:1 between the two-dimensional porous nano-NiFe2O4 and the polyurethane matrix, and stir with a mechanical stirrer for 0.5-2 hours.
[0061] Wherein the precipitant in step 1) is any one or more of glucose, terephthalic acid, and polyvinyl pyrrolidone;
[0062] Wherein the polyester diol in step 2) is any one or more of polybutylene adipate, polyethylene adipate, polycarbonate diol, and polycaprolactone diol;
[0063] Wherein the diisocyanate in step 2) is any one or more of toluene diisocyanate, isophorone diisocyanate, hexanediol diisocyanate, dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate;
[0064] The disulfide in step 2) is any one or more of bis(2-hydroxyethyl) disulfide, bis(10-hydroxydecyl) disulfide, 2,2'-diaminodiphenyl disulfide, bis(11-hydroxyundecyl) disulfide, bis(4-(hydroxymethyl)phenyl) disulfide, and diallyl disulfide;
[0065] Wherein the solvent in step 2) is any one of tetrahydrofuran, acetone, dichloromethane, toluene, dimethylformamide, ether, and dimethylacetamide;
[0066] The catalyst in step 2) is any one of dibutyltin dilaurate, dibutyltin, tetrabutyltin, stannous octoate, and tributyltin chloride.
[0067] The present invention provides a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof. The coating is formed by mixing the two-dimensional porous nano NiFe2O4 and a polyurethane matrix. The specific steps are as follows:
[0068] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is:
[0069] 1.1) 0.952 g nickel chloride hexahydrate (4 mmol) and 2.16 g ferric chloride hexahydrate (8 mmol) were added to 80 ml deionized water; the mixed solution was stirred at 400 rpm for 10 minutes with a magnetic stirrer, and then ultrasonicated for 5 minutes with an ultrasonic machine to form a uniform solution;
[0070] 1.2) adding 0.432 g of glucose (2.4 mmol) to the above metal ion solution, and subjecting the mixed solution to vigorous stirring for 10 minutes and ultrasonic treatment for 5 minutes;
[0071] 1.3) The solution was transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene, sealed, and heated at 150°C for 12 hours;
[0072] 1.5) After the reactor is cooled to room temperature naturally, the solution is poured into a centrifuge tube, and the solid is washed three times with deionized water and anhydrous ethanol alternately at 6000 rpm using a desktop high-speed centrifuge;
[0073] 1.6) Dry the washed powder in a vacuum environment at 60° C. for 12 hours to obtain a black solid powder;
[0074] 1.7) The solid powder was calcined at 800°C for 2 hours at a heating rate of 2°C / min. After natural cooling, the obtained brown powder was the two-dimensional porous nano-NiFe2O4.
[0075] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1, and add the drugs in the following order:
[0076] 2.1) Add 5 g of polybutylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0077] 2.2) Cool down to 70°C, add 10 ml of N,N-dimethylformamide, 1.11 g of isophorone diisocyanate and 0.5 ml of dibutyltin dilaurate dropwise into a three-necked flask, and stir at 400 rpm for 2 hours;
[0078] 2.3) Raise the temperature to 80°C, dissolve 0.62 g of 2,2'-diaminodiphenyl disulfide in the solvent, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 400 rpm for 6 hours;
[0079] 3) Preparation of self-repairing anti-corrosion coating: According to the mass ratio of two-dimensional porous nano-NiFe2O4 to polyurethane matrix of 0.01:1, 0.07 g of two-dimensional porous nano-NiFe2O4 was weighed and added into the above system, and stirred with a mechanical stirrer for 1 hour.
[0080] The above-obtained two-dimensional porous nano NiFe2O4 was characterized and tested:
[0081] from Figure 1 It can be seen that NiFe2O4 has a typical two-dimensional layered structure, stacked layer by layer, similar to the structure of MXene materials. Each layer is composed of several spherical particles with a large number of pores in the middle.
[0082] from Figure 2 It can be seen that the position of the characteristic peaks in the XRD spectrum is consistent with JCPDS#86-2267, indicating that the prepared product is NiFe2O4, and there are no impurity peaks, indicating that there are no impurities, which is consistent with the spinel crystal structure.
[0083] Embodiment 2
[0084] The present invention provides a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof. The coating is formed by mixing the two-dimensional porous nano NiFe2O4 and a polyurethane matrix. The specific steps are as follows:
[0085] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is:
[0086] 1.1) 0.476 g nickel chloride hexahydrate (2 mmol) and 1.08 g ferric chloride hexahydrate (4 mmol) were added to 80 ml deionized water; the mixed solution was stirred at 400 rpm with a magnetic stirrer for 20 minutes, and then ultrasonicated with an ultrasonic machine for 20 minutes to form a uniform solution;
[0087] 1.2) adding 0.216 g of glucose (1.2 mmol) to the above metal ion solution, and subjecting the mixed solution to vigorous stirring for 20 minutes and ultrasonic treatment for 20 minutes;
[0088] 1.3) The solution was transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene, sealed, and heated at 180°C for 18 hours;
[0089] 1.5) After the reactor is cooled to room temperature naturally, the solution is poured into a centrifuge tube, and the solid is washed three times with deionized water and anhydrous ethanol alternately at 6000 rpm using a desktop high-speed centrifuge;
[0090] 1.6) Dry the washed powder in a vacuum environment at 60° C. for 12 hours to obtain a black solid powder;
[0091] 1.7) The solid powder was calcined at 800°C for 2 hours at a heating rate of 2°C / min. After natural cooling, the obtained brown powder was the two-dimensional porous nano-NiFe2O4.
[0092] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1, and add the drugs in the following order:
[0093] 2.1) Add 5 g of polybutylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0094] 2.2) Cool down to 70°C, add 10 ml of N,N-dimethylformamide, 1.11 g of isophorone diisocyanate and 0.5 ml of dibutyltin dilaurate dropwise into a three-necked flask, and stir at 400 rpm for 2 hours;
[0095] 2.3) Raise the temperature to 80°C, dissolve 0.62 g of 2,2'-diaminodiphenyl disulfide in the solvent, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 400 rpm for 6 hours;
[0096] 3) Preparation of self-repairing anti-corrosion coating: According to the mass ratio of two-dimensional porous nano-NiFe2O4 to polyurethane matrix of 0.01:1, 0.07 g of two-dimensional porous nano-NiFe2O4 was weighed and added into the above system, and stirred with a mechanical stirrer for 1 hour.
[0097] The above-obtained two-dimensional porous nano NiFe2O4 was characterized and tested:
[0098] Depend on Figure 3 NiFe2O4 has a typical two-dimensional layered structure, with layers stacked together, similar to the structure of MXene materials. Each layer is composed of several spherical particles with a large number of pores in the middle. Compared with Example 1, the dispersion is better.
[0099] Depend on Figure 4 The corresponding pore size distribution is calculated by the BJH method and is concentrated at 2 nm, indicating that the prepared NiFe2O4 is a mesoporous material. According to the Brunauer-Emmett-Teller (BET) method, the specific surface area of NiFe2O4 is calculated to be 194.67 cm 2 ·g -1 .
[0100] Embodiment 3
[0101] The present invention provides a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof. The coating is formed by mixing the two-dimensional porous nano NiFe2O4 and a polyurethane matrix. The specific steps are as follows:
[0102] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is as follows: 1.1) 0.476g nickel chloride hexahydrate (2mmol) and 1.08g ferric chloride hexahydrate (4mmol) are added into 80ml deionized water; the mixed solution is stirred at 400rpm with a magnetic stirrer for 20 minutes, and then ultrasonicated with an ultrasonic machine for 20 minutes to form a uniform solution;
[0103] 1.2) adding 0.216 g of glucose (1.2 mmol) to the above metal ion solution, and subjecting the mixed solution to vigorous stirring for 20 minutes and ultrasonic treatment for 20 minutes;
[0104] 1.3) The solution was transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene, sealed, and heated at 180°C for 18 hours;
[0105] 1.5) After the reactor is cooled to room temperature naturally, the solution is poured into a centrifuge tube, and the solid is washed three times with deionized water and anhydrous ethanol alternately at 6000 rpm using a desktop high-speed centrifuge;
[0106] 1.6) Dry the washed powder in a vacuum environment at 60° C. for 12 hours to obtain a black solid powder;
[0107] 1.7) The solid powder was calcined at 800°C for 2 hours at a heating rate of 2°C / min. After natural cooling, the obtained brown powder was the two-dimensional porous nano-NiFe2O4.
[0108] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1, and add the drugs in the following order:
[0109] 2.1) Add 5 g of polybutylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0110] 2.2) Cool down to 70°C, add 10 ml of N,N-dimethylformamide, 1.11 g of isophorone diisocyanate and 0.5 ml of dibutyltin dilaurate dropwise into a three-necked flask, and stir at 400 rpm for 2 hours;
[0111] 2.3) Raise the temperature to 80°C, dissolve 0.62 g of 2,2'-diaminodiphenyl disulfide in the solvent, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 400 rpm for 6 hours;
[0112] 3) Preparation of self-repairing anti-corrosion coating: According to the mass ratio of two-dimensional porous nano-NiFe2O4 to polyurethane matrix of 0.01:1, 0.07g of two-dimensional porous nano-NiFe2O4 was added to the above system, and stirred with a mechanical stirrer for 1 hour to obtain a self-repairing anti-corrosion coating named PU-1. It was poured into a polytetrafluoroethylene template and cured at 60°C for 12 hours;
[0113] 4) The self-repairing anti-corrosion coating synthesized above is coated on the surface of a Q235 carbon steel electrode, cured at 60°C for 12 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating electrode.
[0114] The organic coating obtained above was characterized and tested:
[0115] The FTIR spectrum of the PU-1 coating prepared above is as follows: Figure 5 As shown, at 2300cm -1 There is no peak near 3600cm-1 There is no obvious absorption peak nearby, indicating that the -OH group is also nearly completely reacted; the characteristic absorption peak of C=O appears at 1701cm -1 The characteristic absorption peak of carbamate bond -NHCO- appears at 1510cm -1 This strongly suggests that the reaction produced a carbamate bond. -1 The absorption peak at is due to the stretching vibration of CS, which proves the successful introduction of disulfide bonds and indicates that the coating is successfully prepared.
[0116] Embodiment 4
[0117] The present invention provides a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof. The coating is formed by mixing the two-dimensional porous nano NiFe2O4 and a polyurethane matrix. The specific steps are as follows:
[0118] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is:
[0119] 1.1) 0.476 g nickel chloride hexahydrate (2 mmol) and 1.08 g ferric chloride hexahydrate (4 mmol) were added to 80 ml deionized water; the mixed solution was stirred at 400 rpm with a magnetic stirrer for 20 minutes, and then ultrasonicated with an ultrasonic machine for 20 minutes to form a uniform solution;
[0120] 1.2) adding 0.216 g of glucose (1.2 mmol) to the above metal ion solution, and subjecting the mixed solution to vigorous stirring for 20 minutes and ultrasonic treatment for 20 minutes;
[0121] 1.3) The solution was transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene, sealed, and heated at 180°C for 18 hours;
[0122] 1.5) After the reactor is cooled to room temperature naturally, the solution is poured into a centrifuge tube, and the solid is washed three times with deionized water and anhydrous ethanol alternately at 6000 rpm using a desktop high-speed centrifuge;
[0123] 1.6) Dry the washed powder in a vacuum environment at 60° C. for 12 hours to obtain a black solid powder;
[0124] 1.7) The solid powder was calcined at 800°C for 2 hours at a heating rate of 2°C / min. After natural cooling, the obtained brown powder was the two-dimensional porous nano-NiFe2O4.
[0125] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1, and add the drugs in the following order:
[0126] 2.1) Add 5 g of polybutylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0127] 2.2) Cool down to 70°C, add 10 ml of N,N-dimethylformamide, 1.11 g of isophorone diisocyanate and 0.5 ml of dibutyltin dilaurate dropwise into a three-necked flask, and stir at 400 rpm for 2 hours;
[0128] 2.3) Raise the temperature to 80°C, dissolve 0.62 g of 2,2'-diaminodiphenyl disulfide in the solvent, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 400 rpm for 6 hours;
[0129] 3) Preparation of self-repairing anti-corrosion coating: According to the mass ratio of two-dimensional porous nano-NiFe2O4 to polyurethane matrix of 0.03:1, 0.21g of two-dimensional porous nano-NiFe2O4 was weighed and added to the above system, and stirred with a mechanical stirrer for 1 hour to obtain a self-repairing anti-corrosion coating named PU-3. It was poured into a polytetrafluoroethylene template and cured at 60°C for 12 hours;
[0130] 4) The self-repairing anti-corrosion coating synthesized above is coated on the surface of a Q235 carbon steel electrode, cured at 60°C for 12 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating electrode.
[0131] The performance of the organic coating obtained above was tested:
[0132] The temperature rise curve of PU-3 coating within 180s of 1.5W 808nm NIR laser irradiation and the infrared thermal imaging after 180s of irradiation are shown in Figure 2. Figure 6 As shown, the highest temperature can reach 63.3°C, and PU-3 exhibits general photothermal conversion performance.
[0133] After PU-3 coating was irradiated with 1.5W 808nm NIR laser for 180s, the optical photos of the damaged coating and the repaired coating are as follows: Figure 7 PU-3 exhibits general photothermal self-healing performance within 180s. When the coating is scratched, the two-dimensional porous nano-NiFe2O4 converts light into heat after being irradiated by NIR laser, and the coating is locally heated, but the heat is not enough to trigger the reconstruction of dynamic disulfide bonds and reversible hydrogen bonds to completely repair the scratches on the coating.
[0134] Embodiment 5
[0135] The present invention provides a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof. The coating is formed by mixing the two-dimensional porous nano NiFe2O4 and a polyurethane matrix. The specific steps are as follows:
[0136] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is:
[0137] 1.1) 0.476 g nickel chloride hexahydrate (2 mmol) and 1.08 g ferric chloride hexahydrate (4 mmol) were added to 80 ml deionized water; the mixed solution was stirred at 400 rpm with a magnetic stirrer for 20 minutes, and then ultrasonicated with an ultrasonic machine for 20 minutes to form a uniform solution;
[0138] 1.2) adding 0.216 g of glucose (1.2 mmol) to the above metal ion solution, and subjecting the mixed solution to vigorous stirring for 20 minutes and ultrasonic treatment for 20 minutes;
[0139] 1.3) The solution was transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene, sealed, and heated at 180°C for 18 hours;
[0140] 1.5) After the reactor is cooled to room temperature naturally, the solution is poured into a centrifuge tube, and the solid is washed three times with deionized water and anhydrous ethanol alternately at 6000 rpm using a desktop high-speed centrifuge;
[0141] 1.6) Dry the washed powder in a vacuum environment at 60° C. for 12 hours to obtain a black solid powder;
[0142] 1.7) The solid powder was calcined at 800°C for 2 hours at a heating rate of 2°C / min. After natural cooling, the obtained brown powder was the two-dimensional porous nano-NiFe2O4.
[0143] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1, and add the drugs in the following order:
[0144] 2.1) Add 5 g of polybutylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0145] 2.2) Cool down to 70°C, add 10 ml of N,N-dimethylformamide, 1.11 g of isophorone diisocyanate and 0.5 ml of dibutyltin dilaurate dropwise into a three-necked flask, and stir at 400 rpm for 2 hours;
[0146] 2.3) Raise the temperature to 80°C, dissolve 0.62 g of 2,2'-diaminodiphenyl disulfide in the solvent, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 400 rpm for 6 hours;
[0147] 3) Preparation of self-repairing anti-corrosion coating: According to the mass ratio of two-dimensional porous nano-NiFe2O4 to polyurethane matrix of 0.06:1, 0.42g of two-dimensional porous nano-NiFe2O4 was weighed and added to the above system, and stirred with a mechanical stirrer for 1 hour to obtain a self-repairing anti-corrosion coating named PU-6. It was poured into a polytetrafluoroethylene template and cured at 60°C for 12 hours;
[0148] 4) The self-repairing anti-corrosion coating synthesized above is coated on the surface of a Q235 carbon steel electrode, cured at 60°C for 12 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating electrode.
[0149] The performance of the organic coating obtained above was tested:
[0150] The temperature rise curve of PU-6 coating within 180s of 1.5W 808nm NIR laser irradiation and the infrared thermal imaging after 180s of irradiation are shown in the figure below. Figure 8 As shown, the highest temperature can reach 76°C, and PU-6 exhibits excellent photothermal conversion performance.
[0151] After the prepared PU-6 coating was irradiated with 1.5W 808nm NIR laser for 180s, the optical photos of the damaged coating and the repaired coating are as follows: Fig. 9 As shown in Figure 2, PU-6 exhibits excellent photothermal self-healing performance within 180s. When the coating is scratched, the two-dimensional porous nano-NiFe2O4 is irradiated by NIR laser, converting light into heat, and the coating is locally heated to trigger the reconstruction of dynamic disulfide bonds and reversible hydrogen bonds to repair the coating scratches.
[0152] The electrochemical impedance spectroscopy test results of the PU-6 coated electrode after immersion for 60 days are shown in Figure 2. Fig.10 , Fig.11 and Fig.12 As shown in the Nyquist comparison diagram of the original coating, the coating repaired once, and the coating repaired five times, it can be seen that the three curves are all semicircular above the real axis. After the PU-6 coating has undergone five scratch-healing cycles, the |Z| 0.01Hz Still at 10 9 Ωcm 2 The above results prove that PU-6 coating has good long-term protective effect on Q235 carbon steel.
[0153] Embodiment 6
[0154] The present invention provides a method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof. The coating is formed by mixing the two-dimensional porous nano NiFe2O4 and a polyurethane matrix. The specific steps are as follows:
[0155] 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is:
[0156] 1.1) 0.476 g nickel chloride hexahydrate (2 mmol) and 1.08 g ferric chloride hexahydrate (4 mmol) were added to 80 ml deionized water; the mixed solution was stirred at 400 rpm with a magnetic stirrer for 20 minutes, and then ultrasonicated with an ultrasonic machine for 20 minutes to form a uniform solution;
[0157] 1.2) adding 0.216 g glucose (1.2 mmol) to the above metal ion solution, and subjecting the mixed solution to vigorous stirring for 20 minutes and ultrasonic treatment for 20 minutes; 1.3) transferring the solution to a 100 ml stainless steel reactor lined with polytetrafluoroethylene, sealing it, and heating it at 180° C. for 18 hours;
[0158] 1.5) After the reactor is cooled to room temperature naturally, the solution is poured into a centrifuge tube, and the solid is washed three times with deionized water and anhydrous ethanol alternately at 6000 rpm using a desktop high-speed centrifuge;
[0159] 1.6) Dry the washed powder in a vacuum environment at 60° C. for 12 hours to obtain a black solid powder;
[0160] 1.7) The solid powder was calcined at 800°C for 2 hours at a heating rate of 2°C / min. After natural cooling, the obtained brown powder was the two-dimensional porous nano-NiFe2O4.
[0161] 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:1, and add the drugs in the following order:
[0162] 2.1) Add 5 g of polybutylene adipate into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture;
[0163] 2.2) Cool down to 70°C, add 10 ml of N,N-dimethylformamide, 1.11 g of isophorone diisocyanate and 0.5 ml of dibutyltin dilaurate dropwise into a three-necked flask, and stir at 400 rpm for 2 hours;
[0164] 2.3) Raise the temperature to 80°C, dissolve 0.62 g of 2,2'-diaminodiphenyl disulfide in the solvent, treat with ultrasound for 10 minutes, then add dropwise to the three-necked flask, and continue stirring at 400 rpm for 6 hours;
[0165] 3) Preparation of self-repairing anti-corrosion coating: According to the mass ratio of two-dimensional porous nano-NiFe2O4 to polyurethane matrix of 0.1:1, 0.70g of two-dimensional porous nano-NiFe2O4 was weighed and added to the above system, and stirred with a mechanical stirrer for 1 hour to obtain a self-repairing anti-corrosion coating named PU-10. It was poured into a polytetrafluoroethylene template and cured at 60°C for 12 hours;
[0166] 4) The self-repairing anti-corrosion coating synthesized above is coated on the surface of a Q235 carbon steel electrode, cured at 60°C for 12 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating electrode.
[0167] The performance of the organic coating obtained above was tested:
[0168] PU-10 coating shows good noise reduction effect at room temperature, such as Fig.13 As shown, in laboratory tests, the ambient noise was 95dB, and the PU-10 coating was able to reduce the sound pressure to 60dB, effectively reducing the ambient noise by about 37%, proving that the PU-10 coating has a good noise reduction effect.
[0169] The temperature rise curve of PU-10 coating within 180s of 1.5W 808nm NIR laser irradiation and the infrared thermal imaging after 180s of irradiation are shown in the figure below. Fig.14 As shown, the highest temperature can reach 81.7℃, and PU-10 exhibits excellent photothermal conversion performance.
[0170] After the prepared PU-10 coating was irradiated with 1.5W 808nm NIR laser for 180s, the optical photos of the damaged coating and the repaired coating are as follows: Fig.15 As shown in Figure 2, PU-10 exhibits excellent photothermal self-healing performance within 180s. When the coating is scratched, the two-dimensional porous nano-NiFe2O4 is irradiated by NIR laser, converting light into heat, and the coating is locally heated to trigger the reconstruction of dynamic disulfide bonds and reversible hydrogen bonds to completely repair the coating scratches.
[0171] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0172] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating, characterized in that: The coating is prepared by mixing two-dimensional porous nano NiFe2O4 and a polyurethane matrix in a mass ratio of 0.01-0.1:1, and the specific steps are as follows: 1) Synthesis of two-dimensional porous nano-NiFe2O4, the sequence is: 1.1) Weigh nickel chloride hexahydrate and ferric chloride hexahydrate in a molar ratio of 1:2 and dissolve them in 80 ml of deionized water; 1.2) stirring the above solution at a rotation speed of 200-800 rpm for 10-40 minutes, and subjecting the mixed solution to ultrasonic treatment for 5-20 minutes to obtain a mixed metal ion solution; 1.3) adding a precipitant to the above metal ion solution, and repeating the stirring and ultrasonic operation; 1.4) transferring the solution to a sealed reactor for reaction, keeping the temperature in the range of 120-200° C. for 6-18 hours, washing the solution by centrifugation with deionized water and anhydrous ethanol at 6000 rpm for several times after cooling, and vacuum drying the solution at 60° C. for 12 hours to obtain a two-dimensional porous nano NiFe2O4 precursor powder; 1.5) calcining the dried two-dimensional porous nano-NiFe2O4 precursor powder at 800° C. in a tube furnace for 2 hours to obtain a two-dimensional porous nano-NiFe2O4 powder; 2) Synthesis of polyurethane matrix: Weigh polyester diol, diisocyanate and disulfide in a molar ratio of 1:2:
1. The specific operation steps are as follows: 2.1) Add polyester diol into a three-necked flask, heat to 100°C, and apply vacuum for 2 hours to remove moisture; 2.2) Cool down to 70°C, add the solvent, diisocyanate and catalyst dropwise into the three-necked flask, and stir at 300-800 rpm for 1-3 hours; 2.3) Raise the temperature to 80°C, dissolve the disulfide in the solvent, ultrasonicate for 5-10 minutes, then add dropwise to the three-necked flask, and continue stirring at 300-800 rpm for 3-6 hours; 3) Preparation of self-repairing noise reduction and anti-corrosion coating: Add the two-dimensional porous nano-NiFe2O4 to the above polyurethane system in a mass ratio of 0.01-0.1:1 between the two-dimensional porous nano-NiFe2O4 and the polyurethane matrix, and stir with a mechanical stirrer for 0.5-2 hours.
2. The method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating thereof according to claim 1, characterized in that: The polyurethane matrix comprises: The polyester diol is selected from any one or more of polybutylene adipate, polyethylene adipate, polycarbonate diol, and polycaprolactone diol; The diisocyanate is selected from any one or more of toluene diisocyanate, isophorone diisocyanate, hexanediol diisocyanate, dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate; The disulfide is selected from any one or more of bis(2-hydroxyethyl) disulfide, bis(10-hydroxydecyl) disulfide, 2,2'-diaminodiphenyl disulfide, bis(11-hydroxyundecyl) disulfide, bis(4-(hydroxymethyl)phenyl) disulfide, and diallyl disulfide; The solvent is selected from any one of tetrahydrofuran, acetone, dichloromethane, toluene, dimethylformamide, ether, and dimethylacetamide; The catalyst is selected from any one of dibutyltin dilaurate, dibutyltin, tetrabutyltin, stannous octoate and tributyltin chloride.
3. A method for preparing a two-dimensional porous nano NiFe2O4 and a self-repairing noise reduction and anti-corrosion coating, characterized in that: The self-repairing noise reduction and anti-corrosion coating synthesized in claims 1-2 is coated on a metal substrate, cured at 60° C. for 12-24 hours, and cooled to ambient temperature to finally obtain an anti-corrosion organic coating having excellent noise reduction, anti-corrosion and self-repairing properties.
Citation Information
Cited By
Self-repairing wave-absorbing composite material as well as preparation method and application thereof
CN120590785A
Preparation method of modified graphene oxide polyurethane composite material
CN120988463A
Preparation method of modified graphene oxide polyurethane composite
CN120988463B